PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KOTA BATAM - Desrini Ningsih; Selvi Indah Sari (LPPM Universitas Putera Batam, 2018)
This study aims to analyze the influence of investment and labor on the economic growth of Batam City. Data is annual data from 2012 to 2016. The analysis technique used is multiple linear regression, using t test, F test, and classical assumption test. Based on the results of testing the hypothesis obtained that investment has a positive influence on economic growth in the city of Batam with a value of t 3.433 and a significance of 0.001. While the workforce has a negative and significant influence on economic growth in the city of Batam with a t-value of -9.130 and a significant 0,000. Based on the test results, it is known that investment and labor have a positive and significant influence on economic growth in the city of Batam. This is indicated by the calculated value of 101.945 and the significant value of 0.000.